2014
DOI: 10.1152/ajpendo.00177.2014
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 activates glutamine synthetase gene in mouse skeletal muscles through a region downstream of 3′-UTR: possible contribution to ammonia detoxification

Abstract: Skeletal muscle is a reservoir of energy in the form of protein, which is degraded under catabolic conditions, resulting in the formation of amino acids and ammonia as a byproduct. The expression of FOXO1, a forkhead-type transcription factor, increases during starvation and exercise. In agreement, transgenic FOXO1-Tg mice that overexpress FOXO1 in skeletal muscle exhibit muscle atrophy. The aim of this study was to examine the role of FOXO1 in amino acid metabolism. The mRNA and protein expressions of glutami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 34 publications
(63 reference statements)
1
23
0
Order By: Relevance
“…Although entirely speculative at present, these might include FOXO transcription factors previously shown to support GS expression in skeletal muscle and cell lines, as well as FOXP3 expression in T cells (36)(37)(38). The extensive regulation of FOXOs includes feedback loops to control their own transcription and activation as well as FOXP3 within the PTEN/PI3K/Akt/mTOR pathway (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Although entirely speculative at present, these might include FOXO transcription factors previously shown to support GS expression in skeletal muscle and cell lines, as well as FOXP3 expression in T cells (36)(37)(38). The extensive regulation of FOXOs includes feedback loops to control their own transcription and activation as well as FOXP3 within the PTEN/PI3K/Akt/mTOR pathway (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we showed that FOXO1 activates the genes involved in protein degradation (6,7). FOXO1 activates the expression of atrophy-related genes such as atrogin 1 and cathepsin L in various muscle atrophyrelated conditions, including a glucocorticoid treatment (6)(7)(8). These findings suggest that FOXO1 in skeletal muscles plays an important role in muscle atrophy.…”
mentioning
confidence: 71%
“…Specifically, based on data that FOXO1 gene expression is induced by energy deprivation (4), we developed transgenic mice that overexpressed FOXO1 (FOXO1 Tg mice) and showed muscle atrophy (5). In addition, we showed that FOXO1 activates the genes involved in protein degradation (6,7). FOXO1 activates the expression of atrophy-related genes such as atrogin 1 and cathepsin L in various muscle atrophyrelated conditions, including a glucocorticoid treatment (6)(7)(8).…”
mentioning
confidence: 99%
“…Bloom-deficient ES cells, selected for populations of homozygous mutant cells 4 0 0 following mitotic recombination [18], and was listed as a cell line of mouse Bcnt/Cfdp1 knockout cells [21], but the expected cells were not obtained so far (W. Kobayashi, 4 1 3 personal communication). Finally, we were able to assign the signal of endogenous 4 1 4 mBcnt/Cfdp1 detected by two Abs raised against unrelated immunogens.…”
mentioning
confidence: 99%